Retroviral RNA Dimerization: From Structure to Functions - Dubois, Noé; Marquet, Roland; Paillart, Jean-Christophe; Bernacchi, Serena (Frontiers in Microbiology, 2018)
The genome of the retroviruses is a dimer composed by two homologous copies of genomic RNA (gRNA) molecules of positive polarity. The dimerization process allows two gRNA molecules to be non-covalently linked together through intermolecular base-pairing. This step is critical for the viral life cycle and is highly conserved among retroviruses with the exception of spumaretroviruses. Furthermore, packaging of two gRNA copies into viral particles presents an important evolutionary advantage for immune system evasion and drug resistance. Recent studies reported RNA switches models regulating not only gRNA dimerization, but also translation and packaging, and a spatio-temporal characterization of viral gRNA dimerization within cells are now at hand. This review summarizes our current understanding on the structural features of the dimerization signals for a variety of retroviruses (HIVs, MLV, RSV, BLV, MMTV, MPMV…), the mechanisms of RNA dimer formation and functional implications in the retroviral cycle.